An exploratory study examining the relationships between the personal, environmental and activity participation variables and quality of life among young adults with disabilities - Yeung, Polly; Towers, A. (Informa Healthcare, 2014)
Purpose: Despite the apparent importance of International Classification of Functioning, Disability and Health (ICF) framework in influencing the relationships between participation and quality of life (QoL), limited research has been given to comprehensive modelling of their influence. The purpose of this study was to explore the relationships between ICF components, participation factors and QoL among young adults with disabilities. Methods: This study tested a theoretically and empirically based explanatory model on 119 young adults with disabilities to examine how the variables of functional impact, financial behaviour, self-efficacy, neighbourhood environment, social support, social and community participation, satisfaction with participation influenced QoL. Analyses were performed with AMOS maximum likelihood parameter estimation. Results: The final model accepted in this study showed a well-fitted model, which explained 65% of the variance in QoL. Results from the statistical modelling indicated that all the ICF components and satisfaction with participation influenced the level of QoL in young adults with disabilities in either a direct or indirect manner. Conclusions: These findings provide evidence that young adults with disabilities have a very complex interaction of their activity participation, social membership, community connectedness, life satisfaction, suggesting that their context of QoL is shaped by how they make sense not only with their functional status, but also the social and community environment. Current findings further demonstrate that the ICF model of functioning and disability should be thought of as multidimensional and more than instrumental in character when being used by health and rehabilitation professionals.Implications for RehabilitationThis study supports the ICF model to include the concept of QoL as the outcome.Rehabilitation practitioners are encouraged to view the ICF model as multidimensional when designing interventions.Social context and support should be included when developing strategies to enhance QoL in youth transition to adulthood.